Employing arynes in transition-metal-free, N-heterocycles initiated multicomponent reactions - Bhunia, Anup; Biju, Akkattu T. (Synlett, 2014)
Transition-metal-free multicomponent reactions involving arynes, N-heterocycles, and various carbonyl compounds have been reported. With (iso)quinoline as the nucleophile and carbonyl compounds, such as aldehydes, ketones, and N-substituted isatins as electrophiles, the reaction afforded oxazino (iso)quinoline derivatives and the reaction proceeded via 1,4-dipolar intermediates. Interestingly, when the nucleophilic trigger used is pyridine, the reaction furnished indolin-2-one derivatives, and it is probable that the reaction proceeds via a pyridylidene intermediate.
Keywords: arynes - multicomponent reaction - oxindoles - pyridines - quinolines